Architecture of Regol nDalem Mangkubumen - Istiana Adianti (Departement of Architecture, Universitas Islam Indonesia, 2020)
nDalem Mangkubumen is a cultural heritage building that was previously planned as the residence of the Crown Prince, the future king of the Yogyakarta Palace. In 1874 nDalem Mangkubumen was established, and only the Crown Prince Sultan Hamengku Buwono VI had lived in this building for 5-7 years. Currently, nDalem Mangkubumen is used as a place for education and residential areas, so that changes in the shape of buildings and land use. The spatial pattern of nDalem Mangkubumen was developed from the spatial layout of traditional Javanese houses. Still, because nDalem was designed for the Crown Prince, its grandeur was almost similar to the Yogyakarta Palace. As in the traditional Javanese house building intended for relatives of the king, there is a high wall or fence that surrounds the residential complex and a guardrail on each zone. Each fence has a gate that functions as an entrance into the courtyard. This study aims to determine the variation of the gate and which affects the appearance of the gate. So that the results of the study can be used as a reference when maintaining the gate in nDalem Mangkubumen or other nDalem which are mostly owned by the Yogyakarta Palace. Research on changes in the shape, size, and model of the gate using descriptive qualitative research methods by searching data in literature and interviews. nDalem Mangkubumen has a gate with a different size and shape, this change in shape is influenced by the location of the gate and the function of the building that is inside.Keywords: Gate, Regol, Seketeng, Ndalem Mangkubumen, Keraton